Energy savings potential of reversible photothermal windows with near infrared-selective plasmonic nanofilms. (1st July 2022) - Anwar Jahid, Md; Wang, Julian; Zhang, Enhe; Duan, Qiuhua; Feng, Yanxiao
Highlights: Propose a new dynamic window technology that can uncouple solar heat and light. Build and validate an analytical model for windows with nano photothermal effects. Explained the underlying mechanism of dynamic control on the solar heat gain. Incorporate dynamic solar heat gains into parametric building energy simulation. Demonstrate the energy-saving potentials of the reversible photothermal windows. Abstract: A variety of dynamic window and glazing systems with variable solar heat gain control features reacting to seasonal weather conditions and indoor space heating and cooling demands have been investigated in the past several decades. However, the modulation of solar heat gain has to affect the solar light transmittance in most existing dynamic glazing and window systems. In this work, a new type of dynamic window concept was proposed: reversible photothermal windows based on nanoscale solar infrared-induced plasmonic photothermal effects, which can modulate solar heat, independent of visible light conditions. This study provides the underlying technical characteristics and the thermal and optical features under solar irradiation via experimentally validated analytical models. The reversible photothermal windows exhibit a substantial ability to control solar heat gain coefficient with a range between about 0.2 and 0.6 and a stable visible transmittance of 0.32, A whole-building energy simulation demonstrates the potential for energy savings offered by reversible photothermal windows could reach over 18% in mixed climates, as compared to baseline models built using the most recent energy efficiency standards. This research illustrates technical and numerical evidence and mechanisms for energy savings that will support future research and development of this new dynamic window technology.